Integrated pest management goes hand-in-hand with safety - Emily C. Kraus (EDIS)
This publication is geared toward pest management specialists, certified pesticide applicators, and homeowners who are managing indoor and outdoor pests. It provides a broad definition of a pest and describes integrated pest management (IPM) and pest management strategies. As opposed to other EDIS which are specific to management areas (ex: landscape, turf, vegetable) this publication can be used as a basis for all sectors of pest management. The publication also emphasizes using IPM to reduce the development of pesticide resistance and emphasizes how each aspect of IPM contributes to personal and environmental safety.